Canadian perspectives on community development - Todd, Sarah 1971-; Savard, Sébastien 1969- (University of Ottawa Press, 2020)
"Founded in a perspective that speaks to the diversity of contexts and processes used across Canada, this work is nevertheless firmly grounded in theory, offering an in-depth analysis geared toward advanced study in community practice. This depth is further strengthened by the diversity of topics represented in this collective work: community work in various regions of the country exploring issues of poverty and environmental activism; community work with immigrants and refugees, and with trans communities; feminist community organizing as well as organizing with persons with disabilities and with members of linguistic communities; and, finally, arts based community work with the elderly."--
Keywords: Regionalentwicklung; Kanada; Community development / Canada; Développement communautaire / Canada; Community development; Canada; Aufsatzsammlung